2015
DOI: 10.1371/journal.pone.0127691
|View full text |Cite
|
Sign up to set email alerts
|

Novel Features of the Prenatal Horn Bud Development in Cattle (Bos taurus)

Abstract: Whereas the genetic background of horn growth in cattle has been studied extensively, little is known about the morphological changes in the developing fetal horn bud. In this study we histologically analyzed the development of horn buds of bovine fetuses between ~70 and ~268 days of pregnancy and compared them with biopsies taken from the frontal skin of the same fetuses. In addition we compared the samples from the wild type (horned) fetuses with samples taken from the horn bud region of age-matched genetica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 19 publications
(33 reference statements)
5
34
0
1
Order By: Relevance
“…Similar observations have been made for yak fetuses (Li et al ). There is no evidence of ossification in the fetal horn bud (Wiener et al ), and horn growth and ossification occur approximately 1 month after birth (Dove ). Thus, the horn bud differentiates during early fetal development but horn growth does not occur until after the calf is born.…”
Section: Horn Morphology Development and Inheritancementioning
confidence: 99%
See 2 more Smart Citations
“…Similar observations have been made for yak fetuses (Li et al ). There is no evidence of ossification in the fetal horn bud (Wiener et al ), and horn growth and ossification occur approximately 1 month after birth (Dove ). Thus, the horn bud differentiates during early fetal development but horn growth does not occur until after the calf is born.…”
Section: Horn Morphology Development and Inheritancementioning
confidence: 99%
“…Polled fetuses carrying the Celtic variant do not develop horn buds, forming only smooth tissue that is histologically indistinguishable from frontal skin tissue (Allais‐Bonnet et al ; Wiener et al ). Horn bud development is also absent in yak fetuses carrying the Mongolian variant (Li et al ), but has not been investigated in fetuses homozygous for the Friesian and Guarani variants.…”
Section: Polled Genetic Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only limited evidence has been effectively elucidated possibly because of low detection power of microarray-based gene expression profiling platform [ 20 ] or insufficient biological samples subjected to high-throughput mRNA sequencing [ 12 ]. Additionally, it would be very difficult to determine appropriate sampling time points due to the complexity of prenatal horn bud dynamic development [ 13 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…SYNJ1 encodes synaptojanin 1, a key neural protein highly expressed in nerve terminals with essential roles in the regulation of synaptic vesicles in conventional synapses and hair cells [ 30 , 31 ]. Recently, a histological analysis revealed that nervous tissue and hair follicle development have different features in horn buds and polled frontal skin during the development of the horn buds of bovine fetuses, implying that SYNJ1 maybe have an important role in horn differentiation [ 32 ]. PAXBP1 is an essential binding protein that regulates the proliferation of muscle precursor cells, which in turn, are involved in the development of normal craniofacial features and spine morphogenesis [ 33 ].…”
Section: Resultsmentioning
confidence: 99%